O artigo ilustrado : a ilustração editorial nas aulas de desenho do 10º ano - Vieira, Mariana Perry da Câmara (2018)
As teachers of Drawing Class for 10th graders, we had the opportunity to transform a linear and repetitive component, a.k.a. Homework, into moments of investigation and dialogue that the students came to love. We designed a structured week long system which began with the research for contemporary newspaper articles and ended with the student’s subsequent illustration. The results were unexpectedly inspired and the exercise developed into moments of reflection on key issues as well as giving the students a practical means to apply their representational capabilities and work on drawing and communication